An evaluation of UK athletics` clean sport programme in preventing doping in junior elite athletes - Hurst, P.; Ring, C.; Kavussanu, M. (Performance Enhancement & Health, 2020)
UK Athletics` Clean Sport programme reduces the risk of unintentional doping. The programme reduces intentional doping in the short term, but not over 3-months. Similar education programmes may need to be strengthened to ensure effects remain.